2018
DOI: 10.5530/pj.2018.4.102
|View full text |Cite
|
Sign up to set email alerts
|

Renin and Angiotensin Converting Enzyme Inhibition of Standardized Bioactive Fractions of Hyphaene thebaica L. Mart Growing in Egypt

Abstract: Introduction:Hyphaene thebaica L. fruit is known in Egypt for its antihypertensive activity. However a standardized herbal extract/fraction was never prepared. Methods: A biologically guided fractionation was carried out in-vitro for the 50% and 70% ethanol extracts of Hyphaene thebaica L. fruit using the angiotensin converting enzyme (ACE) inhibition and renin inhibition assays. A validated reversed phase HPLC method was developed for the standardization of the active fractions. Results: The ethyl acetate fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…2.1 Biosynthesis process of Eu2O3 using Hyphaene thebaica Hyphaene thebaica L. Mart is locally known as "Doum" native to Upper Egypt and reported in Egyptian traditional medicines [25]. Pytochemical studies indicated that the fruits contain bioactive compounds such as phenols, flavonoids, alkaloids and vitamins [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1 Biosynthesis process of Eu2O3 using Hyphaene thebaica Hyphaene thebaica L. Mart is locally known as "Doum" native to Upper Egypt and reported in Egyptian traditional medicines [25]. Pytochemical studies indicated that the fruits contain bioactive compounds such as phenols, flavonoids, alkaloids and vitamins [26].…”
Section: Methodsmentioning
confidence: 99%
“…The solution was then filtered using Whatman paper n°1, leaving behind transparent aqueous extracts which were used further. The biosynthesis of the Eu2O3 NPs was carried out using already established procedure [25]. Briefly 4 g of the precursor salt Ni(II) nitrate hexahydrate (Eu(NO3)3.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from pneumonia treatment, it's reported that the plant products could also heal other diseases. For instance, cancer (Reda 2011;Bello et al 2017), sunburn, oral ulcers, asthma, skin diseases, premature aging, infertility (Sulieman & Mariod 2019), antihypertensive (Khalil et al 2018), and antiinflammatory, antioxidant, and antimicrobial (Farag & Paré 2013;El-Beltagi 2018) and anti-diabetic (Salib et al 2013). The bone strength cited by the informants could be attributed to the high concentration of Calcium (Ca)…”
Section: Doma and Medicinal Valuementioning
confidence: 99%
“…Some of the economic importance reported include material culture, food and liquor, medicine, firewood, fence, construction, making a raft, etc. (El-Seedi et al 2013;Khalil et al 2018;Stauffer et al 2018;Abdel-Raman 2019;Sulieman & Mariod 2019;Bussmann et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the green synthesis of metal nanoparticles has arisen, which is centered on the utilization of plant extracts as bioreductants. This approach provides safer, easier, faster, more eco-friendly and economical nanoparticles when compared with the physical and chemical approaches and safe alternatives for antimicrobial applications [ 7 , 10 ]. Successful biosynthesis of AgNPs from many plant extracts has been carried out by many authors.…”
Section: Introductionmentioning
confidence: 99%